The effect of learning model inquiry in critical thinking skills course development sociology university students for social education at Islamic University Zainul Hasan Genggong - Aziz Abd.,; Nining Winarsih,; Quthny Aya.,; Rachman Poppy, (Technium Social Sciences Journal, 2020)
Indonesia is the fourth most populous country in the world. Based on projections from the National Development Planning Agency (Bappenas), Indonesia's population in 2018 will reach 265 million people. This number consists of 133.17 million men and 131.88 million women. Judging from the level of population growth, Indonesia is still relatively high. If no effort is made to control it, it will cause many problems. The problem of the Indonesian population in terms of quality is a problem in the ability of its human resources. In Indonesia, the problem of population quality that occurs is influenced by the low level of education, the functions and objectives of education as stipulated in the National Education System Law (UU Sisdiknas No. 20 of 2003 chapter 2 article 3) is to develop the potential of students to become human beings who have faith and devotion to God Almighty, have noble morals. One way to increase the potential of students is to improve students' critical thinking skills. Critical thinking is very important to face changes that are so fast and fast like in the current 4.1 era. The alternative offered in this study to improve students' critical thinking skills is to use the Inquiry learning model. This study used a Quasi Experiment Design (quasi-experimental) with a Non-Equivalent Pretest-Posttest Control Group Design design. In this design, there are two groups, namely the experimental group and the control group. where the selection of the experimental and control groups was not done randomly. The experimental group was the group that received treatment in the form of an inquiry model, while the control group was the group that received Problem Base Learning learning, each of which would be given a pretest and posttest then each treated with treatment